1994
DOI: 10.2307/1941962
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Trace Gas Fluxes and N Availability to Experimentally Elevated Soil Temperatures

Abstract: We are conducting a field study to determine the long—term response of belowground processes to elevated soil temperatures in a mixed deciduous forest. We established 18 experimental plots and randomly assigned them to one of three treatments in six blocks. The treatments are: (1) heated plots in which the soil temperature is raised 5°C above ambient using buried heating cables; (2) disturbance control plots (cables but no heat); and (3) undisturbed control plots (no cables and no heat). In each plot we measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
214
5
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(249 citation statements)
references
References 33 publications
25
214
5
4
Order By: Relevance
“…Neither in CO 2 T-T nor in T-T did soil solution NH 4 concentrations reflect patterns in soil extractable NH 4 ; in CO 2 T-T NH 4 concentrations decreased despite an increase in extractable NH 4 while in T-T soil solution NH 4 increased even though extractable NH 4 did not change. The patterns found in CO 2 T-T were similar to those observed in Harvard forest (Peterjohn et al 1994). Behavior of dissolved NH 4 is more complicated than that of NO 3 since NH 4 more easily adsorbs to the soil than NO 3 ; soil solution NO 3 concentrations were four to five times higher than NH 4 concentrations even though soil extractable NO 3 concentrations were ten times lower.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Neither in CO 2 T-T nor in T-T did soil solution NH 4 concentrations reflect patterns in soil extractable NH 4 ; in CO 2 T-T NH 4 concentrations decreased despite an increase in extractable NH 4 while in T-T soil solution NH 4 increased even though extractable NH 4 did not change. The patterns found in CO 2 T-T were similar to those observed in Harvard forest (Peterjohn et al 1994). Behavior of dissolved NH 4 is more complicated than that of NO 3 since NH 4 more easily adsorbs to the soil than NO 3 ; soil solution NO 3 concentrations were four to five times higher than NH 4 concentrations even though soil extractable NO 3 concentrations were ten times lower.…”
Section: Resultssupporting
confidence: 70%
“…Despite these general patterns, effects of elevated temperature on soil nutrient pools are less clear. Few data are available addressing the effects of warming on soil extractable N. Peterjohn et al (1994) measured increases in soil inorganic N pools in response to warming. Shaw and Harte (2001) measured no increase despite increases in N mineralization rates, which was ascribed to increased plant uptake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While CH 4 uptake often decreases in response to elevated CO 2 and increases in response to warming under wetter soil conditions [Peterjohn et al, 1994;Ineson et al, 1998;Ambus and Robertson, 1999;Phillips et al, 2001;McLain et al, 2002;Sjögersten and Wookey, 2002;McLain and Ahmann, 2008], we observed the opposite during times when soil moisture was below the optimum soil moisture content for CH 4 uptake ( Figure 6). Indeed, CH 4 uptake responses to elevated CO 2 and warming effects were more sensitive under dry soil conditions.…”
Section: Discussionmentioning
confidence: 56%
“…These N additions are within the critical load of N for sensitive ecosystems [8,9]. This N loading may be further exacerbated by increases in N availability from climate influences (i.e., warming and elevated CO 2 ) on internal N cycling, which can increase decomposition, mineralization, and biological nitrogen fixation (BNF) [10][11][12]. The consequences of N loading are well known and include changes in biodiversity [7,13,14], composition [15,16], productivity [17], leaching [18,19], and possibly nitrification [17].…”
Section: Introductionmentioning
confidence: 99%